Effectiveness of sexual offender treatment and reintegration programs: Does program composition and sequencing matter?. Issue 2 (June 2022) - McKillop, Nadine; Hine, Lorelei; Rayment-McHugh, Susan; Prenzler, Tim; Christensen, Larissa S; Belton, Emma
Using administrative data obtained from Queensland Corrective Services, we investigated the composition and sequencing of sex offender treatment and reintegration programs on recidivism outcomes. Outcomes were compared over an average of 4.8 years (SD = 29.20 months; range = 15 days to 9.25 years) on 2, 407 adult males convicted of sexual offences and discharged from custody between 2010 and 2017. Controlling for risk, age, treatment location, and cultural heritage, those who completed a combination of preparatory programs, rehabilitation and reintegration programs were less likely to reoffend and had significantly better survival rates when they did reoffend, compared to those who did not complete—or partially completed—programs. However, reintegration programs, regardless of involvement with other correctional programming, also demonstrated success in reducing short-term recidivism. Combined, these findings indicate that the composition and sequencing of correctional programming likely plays an important role in enhancing outcomes and that engagement in reintegration programs post-incarceration may be pivotal to improving the outcomes for men convicted of sexual offences. Such sequencing, and program composition, warrants further investigation.